Chemical studies on biologically active natural product from medicinal plants in Sabah - Fasihuddin b., Ahmad (Borneo Science, 2000)
ABSTRACT. A concerted e_} j" ort has been undertaken to study the abundant hioiogicai resources of5'abah especiaiiy those with medicinal vaiues in order to discover new drugs for the treatment of diseases. Important source of new drug are those derived from naturai products, and among naturaiiy derived products, piants have proven to be a major source for new pharmacoiogicai agents especiaiiy in treating cancer and AIDS. More then ti-!'}'fl medicinal piants used by various ethnic groups have been documented. Phytochemical studies on some of the selected plants showed interesting results. Studies on Goniothalamus boorneensis resulted in the isolation of goniothalenol, goniotriol, goniothalamin, goniobutenolide A, goniofufurone goniothalesdiol, goniothalactam and aristolactam A-III, all with interesting biological activity and studies on G, velutinus resulted in the isolation of aristololactam-BII abd velutinam with cytotoxic activity. Alstophyline and vilastonine have been isolated from Alstonia scholaris while studies on Litsea pallidifolia resulted in isolation of oxycanthine and obaberine all with antimalarial activity. Users and phytochemical information on some of the plants will be discussed.